1976
DOI: 10.1080/00150197608236693
|View full text |Cite
|
Sign up to set email alerts
|

On a possible unified theory of ferroelectricity

Abstract: A possible unified theory which would describe both "order-disorder" and "displacive" type ferroelectrics is proposed. The ferroelectric phase transitions are considered as a consequence of the dynamical instability of the lattice as well as of the statistical disorder of active (tunnelling) atoms between several equilibrium positions insthe lattice. The self-consistent equations for both order parameters (average displacement and average localization) is obtained and solved numerically. The order of the phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
1

Year Published

1977
1977
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(30 citation statements)
references
References 10 publications
2
27
0
1
Order By: Relevance
“…For a complete description of SPT one has to take into account the both above mentioned mechanisms simultaneously -within the framework of a universal model -as was originally proposed and done in [1,2]. In the next section we are going to present the main features and results of such a description.…”
Section: Preamble: Convenience Of Simple Approximationsmentioning
confidence: 99%
See 4 more Smart Citations
“…For a complete description of SPT one has to take into account the both above mentioned mechanisms simultaneously -within the framework of a universal model -as was originally proposed and done in [1,2]. In the next section we are going to present the main features and results of such a description.…”
Section: Preamble: Convenience Of Simple Approximationsmentioning
confidence: 99%
“…The nature of the SPT described within such a model was examined by applying both the Curie-Weiss (molecular-field) and the self-consistent phonon approximations ([cf. [1,2,7]). By comparing the results of the both approximations it has been shown that for a weak lattice coupling (f 0 ≪ 1) the character of the SPT is of the order-disorder type, which is more consistently described by the molecular-field approximation; for a strong lattice coupling (f 0 ≫ 1) the SPT has to be related to the displacive type, which can be reasonably described by the self-consistent phonon approximation.…”
Section: Preamble: Convenience Of Simple Approximationsmentioning
confidence: 99%
See 3 more Smart Citations